Student Academic Mentoring (SAM): peer support and undergraduate study. - Gillian Pye (Association for Learning Development in Higher Education (ALDinHE), 2016)
University mentoring programmes are increasingly being used to assist and support undergraduate students. Mentoring can take various forms, it may be one to one; face to face; small group or online. It may be between student peers or students and tutors. There is no homogeneous approach and differing mentoring schemes emerge from particular contexts. The purpose of the case study research presented in this paper was to critically evaluate an academic mentoring project that involved year 2 undergraduate students mentoring year 1 students on an education-based degree. The tripartite structural approach involved individual, small group and in-class mentoring. Research data was collected via semi-structured interviews, focus groups, questionnaires and student, mentor and tutor evaluations. The main themes that emerged, following analysis, relate to academic support, socialisation and attrition. Findings also highlight the benefits of a mentoring project that took various forms rather than a singular approach. Scaffolded, collaborative learning, in co-caring communities of practice, appeared to positively affect year 1 student confidence, self-efficacy and motivation. Other benefits included easing the transition from school to university and engendering a sense of belonging.